Pengaruh Kompetensi dan Kualitas Kerja Pegawai terhadap Kepuasan Mitra PT Jamkrida Sumbar (Perseroda) - Middra Silvia; Riri Mayliza (YASIN, 2026)
This study was motivated by the importance of employee competence and work quality in creating partner satisfaction in business-to-business (B2B) relationships. In the cooperation between PT Jamkrida Sumbar (Perseroda) and its partners, employee performance plays a strategic role in maintaining service quality, trust, and the sustainability of business relationships. However, the increasing volume of guarantee services and claim settlement processes creates challenges in maintaining consistent service quality. This study aims to analyze the influence of employee competence and work quality on partner satisfaction at PT Jamkrida Sumbar (Perseroda). This study used a quantitative approach with an associative method. The research population consisted of partners of PT Jamkrida Sumbar (Perseroda), with a sample of 30 respondents selected using purposive sampling. Data were collected through questionnaire distribution and analyzed using multiple linear regression with the assistance of SPSS version 20. The results showed that employee competence and work quality had a positive and significant effect on partner satisfaction. The conclusion of this study affirms that improving employee competence and work quality is an important factor in strengthening satisfaction, trust, and the sustainability of business cooperation between the company and its partners. These findings provide practical implications for PT Jamkrida Sumbar (Perseroda) to continuously improve employee competence and maintain work quality as a strategy for enhancing the quality of guarantee services.